THE ROLE OF GERUNDS AND INFINITIVES IN ENGLISH SENTENCE CONSTRUCTION - Sultonova Nodiraxom Erkinjon qizi (World Scientific Research Journal, 2025)
Annotation. This article explores the grammatical and functional significance of gerunds and infinitives in English sentence construction. The paper analyzes how these two non-finite verb forms function as subjects, objects, and complements in various sentence patterns. Through syntactic examples and descriptive explanation, the article highlights the rules governing their usage and the factors influencing the choice between them. The findings contribute to a better understanding of English verb forms, especially for learners of English as a second or foreign language.